1991
DOI: 10.1080/00140139108967286
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating lifting tasks using subjective and biomechanical estimates of stress at the lower back

Abstract: The objective of this study was to evaluate five different lifting tasks based on subjective and biomechanical estimates of stress at the lower back. Subjective estimates were obtained immediately after the subjects performed the lifting tasks. Rankings for different tasks were obtained according to the perceived level of stress at the lower back. A biomechanical model was used to predict the compressive force at the L5/S1 disc for the weight lifted considering link angles for the particular posture. The tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…To control these losses, ergonomics redesign of MMH tasks has the two fold advantage of accommodating the workplace to a high percentage of the industrial population with and without low back disability (Snook et al, 1978;Benson, 1986Benson, , 1987Snook, 1987;. Acceptable loads and limits in MMH have been analyzed and established using a wide spectrum of techniques including physiological, biomechanical, subjective, observational, focus groups, psychophysical, postural analysis and a combination of the above (Kemper et al, 1990;Kivi and Mattila, 1991;Waikar et al, 1991;Burdorf et al, 1992;Waters et al, 1993;de Looze et al, 1994;Winkel and Mathiassen, 1994;Van der Beek et al, 2005;Bust et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To control these losses, ergonomics redesign of MMH tasks has the two fold advantage of accommodating the workplace to a high percentage of the industrial population with and without low back disability (Snook et al, 1978;Benson, 1986Benson, , 1987Snook, 1987;. Acceptable loads and limits in MMH have been analyzed and established using a wide spectrum of techniques including physiological, biomechanical, subjective, observational, focus groups, psychophysical, postural analysis and a combination of the above (Kemper et al, 1990;Kivi and Mattila, 1991;Waikar et al, 1991;Burdorf et al, 1992;Waters et al, 1993;de Looze et al, 1994;Winkel and Mathiassen, 1994;Van der Beek et al, 2005;Bust et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been conducted in which limits for lifting have been recommended based upon human physical performance of MMH tasks (Ayoub, Dryden, McDaniel, Knipfer, & Dixon, 1979;C., Smith, & Ayoub, 1985;Ciriello, Snook, Blick, & Wilkinson, 1990;Fernandez, Ayoub, & Smith, 1991;Gallagher, 1991;Garg & Ayoub, 1980;Hafez & Ayoub, 1991;Karwowski, 1991;Karwowski & Yates, 1986;Legg & Myles, 1981;Maiti & Ray, 2004;Mital, 1983;Morrissey & Bittner, 1989;Nicholson, 1989;Potvin & Bent, 1997;Sharp & Legg, 1988;Snook & Irvine, 1967;Stalhammar, Louhevaara, & Troup, 1996;Waikar, Lee, Aghazadeh, & Parks, 1991). We found no investigations that examined the impact of aging upon visual perceptions of lifting injury risk.…”
Section: Introductionmentioning
confidence: 92%
“…In 1981 the National Institute for Occupational Safety and Health (NIOSH) in the USA developed guidelines [5] that have been widely cited by studies evaluating lifting tasks [6,7] as providing an indication of acceptable and maximum permissible lifting weights. Indeed, they are referred to in the Royal College of Nursing Code of Practice for the Handling of Patients [3].…”
Section: Outline Of Biomechanical Evaluationmentioning
confidence: 99%
“…In addition, since studies have shown that the handler's subjective estimates of the stress involved in a handling task do not always correspond to the biomechanical predictions [6], it was considered essential to record the nurse's perception of each task through a standardized questionnaire from which subjective data were gathered using Likert and visual analogue scales, together with qualitative comments. This study falls outside the scope of this paper but has been reported elsewhere [4].…”
Section: Additional Recorded Datamentioning
confidence: 99%